Diamond-based composite wave-absorbing material
Through the preparation of diamond-based composite absorbing materials, graphitized diamond composite particles are used for high temperature and high pressure treatment, the problems of insufficient hardness, thermal stability and corrosion resistance of existing absorbing materials in harsh environments are solved, and the aviation industry has been realized. Good application prospects in the aerospace and deep sea fields.
Patent Information
- Application Number
- CN202411256475.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing wave absorbing materials exhibit poor hardness, poor thermal stability, poor corrosion resistance and insufficient wave absorbing performance in harsh environments, making it difficult to meet the needs of light weight, good thermal shielding performance, good corrosion resistance and absorption in aerospace and deep sea fields. Excellent wave performance, excellent mechanical properties and thermal stability.
The preparation method of diamond-based composite wave absorbing material is adopted to form diamond-based composite wave absorbing material with excellent wave absorbing properties through high temperature and high pressure treatment of graphitized diamond composite particles. The material is composed of graphitized diamond composite particles and has high Vickers hardness. , good thermal conductivity, low corrosion current density and high starting oxidation temperature.
It realizes the efficient wave absorption performance of diamond-based composite wave absorption materials in harsh environments, has excellent mechanical properties, thermal shielding properties, corrosion resistance and thermal stability, and is suitable for aerospace and deep-sea fields.
Smart Images

Figure CN119161187A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a diamond-based composite wave absorbing material. Background Art
[0002] Absorbing materials that can resist and weaken electromagnetic radiation have become a research hotspot in the field of materials science.
[0003] The role of absorbing materials in stealth technology is becoming increasingly important. Although traditional metal magnetic absorbing materials have the characteristics of absorbing waves, they have disadvantages such as large mass, poor thermal shielding performance, and poor corrosion resistance; carbon-based absorbing materials and their composite materials with magnetic metal absorbing materials can effectively avoid the above disadvantages, but they have disadvantages such as poor hardness and poor thermal stability; conductive polymer absorbing materials have poor environmental stability and weak mechanical properties, and are not suitable for harsh environments, especially long-term use or exposure conditions; although ceramic absorbing materials have good thermal stability, they also have disadvantages such as large mass and weak absorbing performance.
[0004] Carbon-based materials with different structural morphologies can be constructed as absorbing materials through different preparation methods to improve the absorbing properties of absorbing materials. It is expected that carbon-based absorbing materials with stable absorbing properties in harsh environments can be obtained to meet the needs of aerospace and deep-sea fields for absorbing materials with light weight, good thermal shielding properties, good corrosion resistance, excellent absorbing properties, excellent mechanical properties and thermal stability. Summary of the invention
[0005] In view of this, some embodiments disclose a diamond-based composite absorbing material, which is obtained by a method for preparing a diamond-based composite absorbing material, wherein the diamond-based composite absorbing material is prepared from graphitized diamond composite particles, and the graphitized diamond composite particles are composed of a diamond matrix and a graphene layer on the surface of the diamond matrix; wherein the effective absorption bandwidth of the diamond-based composite absorbing material is between 2.6 and 4 GHz, and the minimum reflection loss value is between -30 and -61.47 dB; the effective absorption frequency of the diamond-based composite absorbing material with a thickness of 1.5 to 5.5 mm is between 4.28 and 18 GHz;
[0006] The Vickers hardness of diamond-based composite absorbing materials is between 40 and 60 GPa, the thermal conductivity at room temperature is between 3.4 and 3.7 W / m·K, and the corrosion current density is between 10 -6 ~10 -7 A / cm 2 The self-corrosion potential is between -200 and 0 mV, and the initial oxidation temperature is between 1100 and 1250 °C.
[0007] Further, some embodiments disclose a method for preparing a diamond-based composite absorbing material, comprising the steps of:
[0008] S1, graphitizing the surface of the nano-diamond particles to obtain graphitized diamond composite particles;
[0009] S2, compression molding the graphitized diamond composite particles to obtain a diamond-based composite absorbing material blank;
[0010] S3. The diamond-based composite absorbing material blank is subjected to high temperature and high pressure treatment to obtain a diamond-based composite absorbing material.
[0011] Furthermore, the method for preparing the diamond-based composite absorbing material disclosed in some embodiments further includes the steps of:
[0012] S4. Treat the diamond-based composite absorbing material with an acid solution.
[0013] The diamond-based composite absorbing material disclosed in the embodiment of the present invention is prepared from graphitized diamond composite particles. The amorphous carbon on the surface of the diamond particles is graphitized to obtain diamond-based composite particles. The diamond-based composite particles are further subjected to high temperature and high pressure treatment to obtain a diamond-based composite absorbing material with excellent absorbing performance. At 5.5 mm, the minimum reflection loss value reaches -61.47 dB, and at 2.7 mm, the widest effective absorption bandwidth can reach 4.0 GHz. The sample also has excellent mechanical properties, thermal shielding properties, corrosion resistance, thermal stability, etc. Its Vickers hardness is between 40 and 60 GPa, which is a superhard material. The room temperature thermal conductivity is between 3.4 and 3.7 W / m·K, the initial oxidation temperature is between 1100 and 1250°C, and the corrosion current density is between 10 -6 ~10 -7 A / cm 2 The self-corrosion potential is between -200 and 0 mV, and the corrosion rate is between 0.001 and 0.005 mm / a. It is a very corrosion-resistant material and has good application prospects in aerospace and deep-sea fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a photo of the diamond-based composite absorbing material sample disclosed in Example 1;
[0015] Figure 2 This is a diagram of the wave absorbing performance of the diamond-based composite wave absorbing material sample disclosed in Example 1;
[0016] Figure 3 This is a diagram of the wave absorbing performance of the diamond-based composite wave absorbing material sample disclosed in Example 2;
[0017] Figure 4 This is a diagram of the wave absorbing performance of the diamond-based composite wave absorbing material sample disclosed in Example 3;
[0018] Figure 5 A three-dimensional diagram of the absorbing performance of the diamond-based composite absorbing material sample disclosed in Example 3;
[0019] Figure 6 TEM image of the diamond-based composite absorbing material sample disclosed in Example 3;
[0020] Figure 7 It is a comprehensive comparison chart of multiple properties of the diamond-based composite absorbing material samples disclosed in Examples 1 to 3 and other absorbing materials. DETAILED DESCRIPTION
[0021] The word "embodiment" used herein as an "exemplary" does not necessarily mean that any embodiment described is superior or better than other embodiments. Performance index tests in the embodiments of the present invention are performed using conventional test methods in the art unless otherwise specified. It should be understood that the terms described in the embodiments of the present invention are only used to describe specific implementation methods and are not intended to limit the contents disclosed in the embodiments of the present invention.
[0022] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the embodiments of the present invention belong; other experimental methods and technical means not specifically specified in the embodiments of the present invention refer to experimental methods and technical means commonly used by ordinary technicians in the field.
[0023] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values clearly listed as the limits of the range, but also all independent values or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values of 1% to 5%, but also the independent values and sub-ranges within the range shown. Therefore, independent values such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described.
[0024] In this document, including in the claims, transitional words such as "comprises," "includes," "with," "having," "containing," "involving," "accommodating," etc. are understood to be open-ended, i.e., meaning "including but not limited to." Only the transitional words "consisting of" and "composed of" are closed transitional words.
[0025] In order to better illustrate the present invention, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the gist of the present invention.
[0026] Under the premise of no conflict, the technical features disclosed in the embodiments of the present invention may be arbitrarily combined, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present invention.
[0027] In some embodiments, a method for preparing a diamond-based composite absorbing material comprises the steps of:
[0028] S1. Graphitizing the surface of the nano-diamond particles to obtain graphitized diamond composite particles; usually, the surface of the nano-diamond particles contains a certain amount of amorphous carbon. During the graphitization process, part of the amorphous carbon is oxidized and disappears, and the remaining amorphous carbon undergoes graphitization transformation at high temperature, and the amorphous carbon is converted into a graphite layer, that is, a few layers of graphene are covered on the surface of the diamond matrix; the diamond matrix particles covered with a few layers of graphene are graphitized diamond composite particles;
[0029] In some embodiments, the graphitization of nanodiamond particles includes:
[0030] S101, heat treating the nano-diamond particles at 450-550° C. in an air atmosphere; as an optional embodiment, the air atmosphere is flowing air, and the flow rate is set to 10-30 Sccm;
[0031] S102, performing vacuum heat treatment on the heat-treated nano-diamond particles at 1000-1200° C. to obtain graphitized nano-diamond composite particles;
[0032] S2, compression molding the graphitized diamond composite particles to obtain a diamond-based composite absorbing material blank; usually, during the compression molding process, the graphitized diamond composite particles are closely interlocked and stacked with each other to form a diamond-based composite absorbing material blank with a set shape;
[0033] S3. The diamond-based composite absorbing material blank is subjected to high temperature and high pressure treatment to obtain a diamond-based composite absorbing material. Usually, during the high temperature and high pressure treatment of the diamond-based composite absorbing material blank, the graphitized diamond composite particles are further interlocked with each other, and the graphene layers distributed on the surface of the diamond matrix particles are embedded and fused with each other to form interwoven graphene layers. The interwoven graphene layers have good electrical conductivity and can produce electrical conductivity losses, so they have good absorbing performance. Based on the excellent physical and chemical properties of the diamond matrix in the diamond-based composite absorbing material and the good electrical conductivity of the graphene layer, the diamond-based composite absorbing material not only has good absorbing performance, but also has excellent mechanical properties, thermal properties and corrosion resistance, and presents good comprehensive performance in harsh environments. Usually, the pressed diamond-based composite absorbing material blank is placed in the cylindrical cavity of the pressing mold, so that the diamond-based composite absorbing material blank is filled into the hollow cylindrical cavity, and then subjected to high temperature and high pressure treatment in a six-sided top press. After treatment under the set temperature and pressure conditions, the six-sided top press is depressurized to take out the diamond-based composite absorbing material coated in the pressing mold. Usually, the pressing mold used for the six-sided top press is composed of a zirconium cup and a molybdenum cup.
[0034] In some embodiments, the temperature of the high temperature and high pressure treatment of the diamond-based composite absorbing material blank is set to 1100-1300° C., and the pressure is set to 7-9 GPa.
[0035] The method for preparing the diamond-based composite absorbing material disclosed in some embodiments further includes the steps of:
[0036] S4, treating the diamond-based composite absorbing material with an acid solution. Usually, the prepared diamond-based composite absorbing material is wrapped by a pressing mold, and the pressing mold needs to be dissolved and removed by treating with an acid solution.
[0037] In some embodiments, the acid solution is a mixed solution of sulfuric acid and nitric acid, wherein the molar ratio of sulfuric acid to nitric acid is 1:1-4.
[0038] In some embodiments, the diamond-based composite absorbing material is boiled in an acid solution at a temperature of 150 to 210° C. for a time of 2 to 4 hours.
[0039] The diamond-based composite absorbing material disclosed in some embodiments is obtained by a preparation method of the diamond-based composite absorbing material, wherein the diamond-based composite absorbing material is prepared from graphitized diamond composite particles, and the graphitized diamond composite particles are composed of a diamond matrix and a graphene layer on the surface of the diamond matrix; the effective absorption bandwidth of the diamond-based composite absorbing material is between 2.6 and 4 GHz, and the minimum reflection loss value is between -30 and -61.47 dB; the effective absorption frequency of the diamond-based composite absorbing material with a thickness of 1.5 to 5.5 mm is between 4.28 and 18 GHz; the Vickers hardness of the diamond-based composite material is between 40 and 60 GPa, the thermal conductivity at room temperature is between 3.4 and 3.7 W / m·K, and the corrosion current density is between 10 -6 ~10 - 7 A / cm 2 The self-corrosion potential is between -200 and 0 mV, and the initial oxidation temperature is between 1100 and 1250 °C.
[0040] The technical details are further illustrated below in conjunction with embodiments.
[0041] Example 1
[0042] The method for preparing the diamond-based composite absorbing material disclosed in Example 1 includes:
[0043] S1. Place ordinary nanodiamonds in a tubular furnace and heat treat them in an air atmosphere at 450°C for 60 minutes, so that some amorphous carbon on the surface is oxidized and disappears. Then, the air atmosphere in the tubular furnace is replaced with a vacuum environment, and vacuum heat treatment is performed at 1200°C to graphitize the surface, thereby obtaining graphitized nanodiamond composite particles;
[0044] S2. Pour the graphitized nano-diamond composite particles into a mold, and use a cold press to compress the graphitized nano-diamond composite particles into a cylindrical sample with a diameter of 15.1 mm and a height of 4.7 mm; then put the cylindrical sample into a cylindrical cavity made of a zirconium cup and a molybdenum cup, so that the sample is fully filled into the cylindrical cavity;
[0045] S3, subjecting the cylindrical sample to high temperature and high pressure treatment using a six-sided top press, with the pressure and power of the six-sided top press set to 70 MPa, 8.2 kW (7 GPa, 1100° C.), and taking out the cylindrical sample after the six-sided top press is depressurized;
[0046] S4. The hot-pressed cylindrical sample is placed in a prepared mixed solution of sulfuric acid and nitric acid for acid boiling at a heating temperature of 210° C. for 4 hours to obtain a diamond-based composite absorbing material sample.
[0047] Figure 1This is a photo of the diamond-based composite absorbing material sample disclosed in Example 1; the diamond-based composite absorbing material is prepared from graphitized diamond composite particles, and the graphitized diamond composite particles are composed of a diamond matrix and a graphene layer coated on the surface of the diamond matrix; disordered few-layer graphene inside the material is embedded between the nanodiamond matrix.
[0048] The coaxial method was used to test the wave absorption of the diamond-based composite wave absorbing material sample prepared in Example 1, and the reflection loss values of the samples with different thicknesses were tested. Figure 2 As shown, when the thickness is 9 mm, the minimum reflection loss value of the sample reaches -63.57 dB, and when the thickness is 6 mm, the widest effective absorption bandwidth is 2.6 GHz.
[0049] Example 2
[0050] The method for preparing the diamond-based composite absorbing material disclosed in Example 2 refers to Example 1; wherein, in step S2, the pressure and power of the press are set to 70 MPa and 8.3 kW (7 GPa and 1200° C.).
[0051] The coaxial method was used to test the wave absorption of the diamond-based composite wave absorbing material sample prepared in Example 2, and the reflection loss values of the samples with different thicknesses were tested. Figure 3 As shown, when the thickness is 2.6 mm, the minimum reflection loss value of the sample reaches -28.93 dB, and when the thickness is 2.9 mm, the widest effective absorption bandwidth is 3.5 GHz.
[0052] Example 3
[0053] The method for preparing the diamond-based composite absorbing material disclosed in Example 3 refers to Example 1; wherein, in step S2, the pressure and power of the press are set to 70 MPa and 8.4 kW (7 GPa and 1300° C.).
[0054] The coaxial method was used to test the absorption of the diamond-based composite absorbing material sample prepared in Example 3, and the reflection loss values of the samples with different thicknesses were tested. Figure 4 and Figure 5 As shown, when the thickness is 5.5 mm, the minimum reflection loss value of the sample reaches -61.47 dB, and when the thickness is 2.7 mm, the widest effective absorption bandwidth is 4.0 GHz. Figure 6 This is a TEM image of the diamond-based composite absorbing material disclosed in Example 3.
[0055] In the embodiment, the coaxial method is used to test the sample using a vector network analyzer (Agilent E5071C). The outer diameter of the coaxial ring sample is 7 mm and the inner diameter is 3.07 mm. The test needs to select a test range of 1 to 18 GHz, and use python software to process the data and calculate its reflection loss value.
[0056] Figure 7 The figure is a comprehensive comparison of multiple properties of the diamond-based composite absorbing material samples disclosed in Examples 1 to 3 and other samples. Compared with the absorbing materials in the prior art, such as carbon nanotube composite materials, reduced graphene oxide composite materials, onion carbon, ceramic composite materials and carbon fiber composite materials, the mechanical properties, thermal stability, thermal shielding properties and corrosion resistance of the diamond-based composite absorbing materials disclosed in Examples 1 to 3 are at a relatively high level, with a Vickers hardness between 40 and 60 GPa, belonging to superhard materials, a room temperature thermal conductivity between 3.4 and 3.7 W / m·K, an initial oxidation temperature between 1100 and 1250°C, and a corrosion current density between 10 -6 ~10 -7 A / cm 2 The self-corrosion potential is between -200 and 0 mV, and the corrosion rate is between 0.001 and 0.005 mm / a. It is a very corrosion-resistant material.
[0057] The method for preparing a diamond-based composite absorbing material disclosed in an embodiment of the present invention graphitizes amorphous carbon on the surface of diamond particles to obtain diamond-based composite particles, and further subjects the diamond-based composite particles to high temperature and high pressure treatment to obtain a diamond-based composite absorbing material with excellent absorbing performance, which has good application prospects in the fields of aerospace and deep sea.
[0058] The technical solutions disclosed in the embodiments of the present invention and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of the present invention and do not constitute a limitation on the technical solutions of the embodiments of the present invention. Any conventional changes, replacements or combinations of the technical details disclosed in the embodiments of the present invention have the same inventive concept as the present invention and are within the protection scope of the claims of the present invention.
Claims
1. Diamond-based composite absorbing material, characterized in that: The diamond-based composite absorbing material is prepared from graphitized diamond composite particles, and the graphitized diamond composite particles are composed of a diamond matrix and a graphene layer on the surface of the diamond matrix; The effective absorption bandwidth of the diamond-based composite absorbing material is between 2.6 and 4 GHz, and the minimum reflection loss value is between -30 and -61.47 dB; the effective absorption frequency of the diamond-based composite absorbing material with a thickness of 1.5 to 5.5 mm is between 4.28 and 18 GHz; the Vickers hardness of the diamond-based composite material is between 40 and 60 GPa, the thermal conductivity at room temperature is between 3.4 and 3.7 W / m·K, and the corrosion current density is between 10 -6 ~10 -7 A / cm 2 The self-corrosion potential is between -200 and 0 mV, and the initial oxidation temperature is between 1100 and 1250 °C.
2. The diamond-based composite absorbing material according to claim 1, characterized in that: The method for preparing the diamond-based composite absorbing material comprises the following steps: S1, graphitizing the surface of the nano-diamond particles to obtain graphitized diamond composite particles; S2, compression molding the graphitized diamond composite particles to obtain a diamond-based composite absorbing material blank; S3. The diamond-based composite absorbing material blank is subjected to high temperature and high pressure treatment to obtain a diamond-based composite absorbing material.
3. The diamond-based composite absorbing material according to claim 2, characterized in that: The preparation method also includes the steps of: S4. Treat the diamond-based composite absorbing material with an acid solution.
4. The diamond-based composite absorbing material according to claim 2, characterized in that: Step S1 specifically includes: S101, heat treating the nano-diamond particles at 450-550° C. in an air atmosphere; S102, the heat-treated nano-diamond particles are subjected to vacuum heat treatment at 1000-1200°C to obtain graphitized nano-diamond composite particles.
5. The diamond-based composite absorbing material according to claim 2, characterized in that: In step S101 , the air atmosphere is flowing air, and the flow rate is set to 10 to 30 Sccm.
6. The diamond-based composite absorbing material according to claim 2, characterized in that: In step S3, the temperature of the high temperature and high pressure treatment of the diamond-based composite absorbing material blank is set to 1100-1300° C., and the pressure is set to 7-9 GPa.
7. The diamond-based composite absorbing material according to claim 3, characterized in that: In step S4, the acid solution is a mixed solution of sulfuric acid and nitric acid, wherein the molar ratio of sulfuric acid to nitric acid is 1:1-4.
8. The diamond-based composite absorbing material according to claim 3, characterized in that: In step S4, the diamond-based composite absorbing material is boiled in an acid solution at a temperature of 150 to 210° C. for 2 to 4 hours.
Citation Information
Patent Citations
Method of manufacturing a diamond composite and a composite produced by same
CA2342986A1
Composite super-hard material and synthetic method thereof
CN109400160A
Three-dimensional heat-conducting and wave-absorbing reinforced composite film and preparation method thereof
CN114031074A
Method of manufacturing a diamond composite and a composite produced by same
CN1320108A
Electromagnetic and radiation shielding using nanoforests
US12225701B1
Cited By
Graphene and diamond filler polymer composite material as well as preparation method and application thereof
CN121851716A
